Seroprevalence of Avian H9N2 Influenza Virus in a Population of Iranian Domestic Dogs - Mohammad Abbaszadeh Hasiri; Saeed Nazifi; Elham Mohsenifard; Maryam Ansari-Lari (Journal of Basic & Applied Sciences, 2021)
The prevalence of H9N2 influenza virus in dogs was first time observed in Fars province of Iran. A total of 182 dogs were selected from the clinical cases at the Small Animal Clinic of Veterinary Medicine School, Shiraz University. After obtaining history, physical examination was performed and blood samples were obtained for serological examination (Eliza and HI assay) for the detection of H9N2-specific antibodies. Associated factors (age, breed, diet, place, presence of other dogs, general symptoms, respiratory and gastrointestinal signs) were also evaluated. The positive results showed that 81.7 % of ELISA positive cases had titer ? 32 for H9N2 influenza in HI test. Although positive result were found more in dogs with general or respiratory signs, no significant differences were observed in the evaluated factors and seropositivity. This research showed high seroprevalence of Ab against H9N2 in dogs and made this hypothesis that H9N2 may be important in dogs in virus persistence. Additional research is needed for detection of epidemiologic role of dogs in transmission and pathogenesis of H9N2 in dogs and humans.